Czech Republic: Independent Tax Policy as a Part of Czech Fiscal Policy - Radvan, Michal (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
Tax issues are often considered crucial to public financing. Many state policies depend on tax revenue. The state sets its tax policy to collect adequate income in order to ensure the management of the state and local self-government units. The position of tax law within the system of law is perceived in a variety of ways in the world and in European Union (EU) Member States. For example, in Western European countries (the old EU Member States), tax law and tax law science have long-standing traditions. Tax law is an independent branch of European law. In the new EU Member States (Central and Eastern Europe), tax law is (still) a sub-branch of financial law according to the local legal sciences; specifically, it pertains to the fiscal part of financial law, which deals with the legal relationships created, implemented, and terminated in the process of creating, distributing, and using public monetary funds. The fiscal part of financial law includes, in addition to tax law (public budget revenues), budgetary law, and public subsidy law (public budget expenditures). This chapter addresses the position and role of tax laws in the Czech legal system. The following sections identify the pros and cons of tax sovereignty and tax harmonisation in tax law regulations and reviews notable efforts in the tax avoidance field. The last section presents the conclusions and de lege ferenda recommendations.Keywords: Czech tax law, self-application in taxation, tax sovereignty, tax harmonisation, tax avoidance